2016
DOI: 10.3758/s13415-016-0457-9
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological dissociation of craving and stimulus-dependent attentional capture in smokers

Abstract: It has been suggested that over the course of an addiction, addiction-related stimuli become highly salient in the environment, thereby capturing an addict's attention. To assess these effects neurally in smokers, and how they interact with craving, we recorded electroencephalography (EEG) in two sessions: one in which participants had just smoked (noncraving), and one in which they had abstained from smoking for 3 h (craving). In both sessions, participants performed a visual-search task in which two colored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…As we found previously (Donohue, Woldorff, et al, ), craving has a general effect on overall arousal. Here, when we examined the effects of craving on the P1 component in response to the cue stimuli, we found that this component was (marginally) enhanced when participants were in a state of craving.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As we found previously (Donohue, Woldorff, et al, ), craving has a general effect on overall arousal. Here, when we examined the effects of craving on the P1 component in response to the cue stimuli, we found that this component was (marginally) enhanced when participants were in a state of craving.…”
Section: Discussionsupporting
confidence: 88%
“…That is, craving could still operate in a non‐specific manner, altering all attention and cognitive control processes, with behavioural ramifications only showing up for certain cognitive control tasks. In a previous study (Donohue, Woldorff, et al, ), we observed that when smokers were in a state of craving, they had an enhanced sensory‐evoked P1, suggesting a higher general level of arousal. Surprisingly, this had no consequences for an attentional‐shift‐related task, with smokers showing comparable behavioural and neural effects in both sated and craving conditions.…”
Section: Introductionmentioning
confidence: 46%
See 1 more Smart Citation
“…That is, a larger N2pc, typically associated with a stronger focusing onto the target and potentially reflecting better distractor suppression ( Mazza et al. 2009 ; Donohue et al. 2016 ), might have partially compensated for the MW.…”
Section: Discussionmentioning
confidence: 99%
“…The specific task used was a rare‐target detection task, to which subjects only had to make a response about 10% of the time, enabling us to examine the responses to the non‐target stimuli (standards) without any contamination from motor‐related activity, while still having the target‐related responses present on a small percentage of trials. In response to the target stimuli, we predicted to see that the P300 component, previously observed to be insensitive to the probability of a reward in addicts (Morie et al ., ), would not be sensitive to the task conditions (purportedly bringing participants closer to or farther away from their reward of smoking), but might rather show an enhancement in the craving condition during which overall arousal may have been higher (Donohue et al ., ). In response to the standard stimuli, we expected to see a frontal component similar to a cue‐related negativity (Morie et al ., , ), with such a negative process likely having an extended duration, as has been observed in addicts in a response to substance‐related cues (Littel et al ., ) that likely induce craving (Carter & Tiffany, ).…”
Section: Introductionmentioning
confidence: 97%